2019
DOI: 10.24874/ti.2019.41.03.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Different Percentage of Pour Point Depressant (PPD) On the Tribological Properties of Palm Kernel Oil

Abstract: A research has been done to investigate the tribological performance of palm kernel oil (PKO) with addition of different percentage of pour point depressant, PPD (5w%, 10wt%, 20wt% and 30wt%) according to ASTM D2783. The main analyses that have been done in this research are low temperature performance ability of blended PKO, coefficient of friction (COF), wear scar diameter (WSD) and surface profile. The result of the experiment has shown that for low temperature performance, PKO with 20wt%PPD (A2-20%) and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
1
3
1
Order By: Relevance
“…Hence, the significant thermal stability and cold temperature properties of the PKO biolubricants, compared with the PKO. Similar results were obtained by Alang et al, 1 Bahadi et al, 12 Shaba et al, 16 Dandan et al, 51 and Musa 49 for the synthesis of biolubricant using PKO; as well as by Ishola et al 14 and Bello et al, 53 for the synthesis of biodiesel from palm olein and PKO, respectively.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Hence, the significant thermal stability and cold temperature properties of the PKO biolubricants, compared with the PKO. Similar results were obtained by Alang et al, 1 Bahadi et al, 12 Shaba et al, 16 Dandan et al, 51 and Musa 49 for the synthesis of biolubricant using PKO; as well as by Ishola et al 14 and Bello et al, 53 for the synthesis of biodiesel from palm olein and PKO, respectively.…”
Section: Resultssupporting
confidence: 73%
“…The viscosity of the PKO sample was lower than the values reported for PKO, by Alang et al 1 The viscosity was also lower than the value for Jatropha and palm oils by Menkiti et al, 4 and Reddy et al, 50 respectively. These values for PKO biolubricant samples were less than those of biolubricant from PKO reported as 480.63 cSt at 40°C and 20.54 cSt at 100°C, by Alang et al 1 Similarly, the values of viscosities at 40 and 100°C for PKO biolubricant samples in this study were higher than the 32.67 and 6.10 cSt, respectively, reported for palm kernel biolubricant by Shaba et al 16 Furthermore, Bahadi et al 12 and Dandan et al, 51 reported that the viscosities of palm kernel biolubricants at 40 and 100°C as, 41.76, 8.73 cSt and 35.36, 11.24 cSt, respectively. These cited values were relatively close to the values obtained in this work.…”
Section: Resultscontrasting
confidence: 58%
“…The results have shown that on adding PPD, the stated biolubricant is capable of withstanding lower temperatures. 140 The addition of ZnO nanoparticles in optimized concentration blended in neem oil prevents the rise in viscosity, clearly manifesting ZnO as a pour point depressant at subzero temperature. 141 3.3.7.…”
Section: Pour Point Depressants (Ppds)mentioning
confidence: 99%
“…Beyond this, many other researchers have worked on palm oil and some other vegetable oils in prospecting biodegradable lubricants. Dandan & Syahrullail (2017) demonstrated that palm oil can be applied for lubrication in sensitive operations due to their nontoxicity. Distinct lubricity of palm oil at low temperature is a potential for its preference upon other vegetative seed oils.…”
Section: Potentials and Limitations Of Vegetable Oilmentioning
confidence: 99%